The last family - Valkov, Atanas 1982- (Matchbox Films, 2017)
"The story of a well-known artistic family: legendary painter Zdzislaw Beksinski, his wife Zofia and their son Tomasz, a highly-praised music critic and translator. Their lives were far from being usual." [imdb.com]
Original: Polen 2016
Bildformat 2.38:1 (16:9)
Keywords: Film; DVD-Video